(untitled) (PERcursos Linguísticos, 2021)
It is extensively discussed the importance of raising current issues in the classroom environment to mould critical students who can really participate in society. However, how can a meaninful text approach be developed nowadays? What are the challenges for those who take texts as their teaching object? Considering these questions, based on the theoretical principles of Charaudeau’s Semiolinguistics Discourse Analysis perspective, the main purpose of the present study is to analyze the argumentative construction and the sociodiscursive imaginaries in comic strips featuring Armandinho and in a journalistic text about privatization. By analyzing the construction of arguments and counterarguments and the sociodiscursive imaginaries which produce favorable and unfavorable discourses about privatization, this text is intended to contribute to the teaching and learning of the indirect signification comprehension (CHARAUDEAU, 2018) and, as a consequence, to the formation of critical readers.